Best Answer

9s+6s-12s=24... Ignore the 's' for a moment giving the sum 9+6-12=24 - This results in the answer 3 x 'something' = 24. Therefore s=8 !

Q: How do you solve 9s plus 6s-12s equals 24?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5x+3+x=24 6x+3=24 6x=21 x=3.5

To solve for x you would first subtract 24 from each side. You would then divide both sides by 2. The answer is x=(y-24)/2

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

15 + n = 24 (subtract 15 from both sides) n = 9

2x/3 = 8 + 4x2x = 24 + 12x-24 = 10x-2.4 = x

Related questions

24

2z+6z+24=0 8z+24=0 8z= -24 z= - 3

5x+3+x=24 6x+3=24 6x=21 x=3.5

To solve for x you would first subtract 24 from each side. You would then divide both sides by 2. The answer is x=(y-24)/2

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

15 + n = 24 (subtract 15 from both sides) n = 9

-2x = -4x + 24 -2x + 4x = 24 2x = 24 x = 24/2 x = 12

5 plus 25 equals 60. Need to solve for 5 plus 25 equals ?: 2 plus 10 equals 24 is equivalent to 2 × (1 plus 5) equals 2 × (12); and 3 plus 15 equals 36 is equivalent to 3 ×(1 plus 5) equals 3 × (12); thus 5 plus 25 equals ? is equivalent to 5 × (1 plus 5) equals 5 × (12); thus ? = 5 × 12 = 60.

7x+6 = -3x-24 7x+3x = -24-6 10x = -30 x = -3

2x/3 = 8 + 4x2x = 24 + 12x-24 = 10x-2.4 = x

4368/24 = 182 24 x 14 x 13 = 4368

To solve for x: 2x2 + 10 = 58 2x2 = 48 x2 = 24 x = √24 x = √4 × √6 x = 2√6